Anti-networking and digital technology animosity as a challenge in postmodern organization - Jiménez Rodríguez, Luis Alfredo; Gamboa Suárez, Ramiro; Garcia Mogollón, Javier Mauricio (Ingeniería Solidaria, 2025)
Purpose: The preceding construct served as a central element in fully identifying the benefits and alternatives for transforming a conventional organization into an intelligent organization through the proper implementation of technology.Method: The study employed a qualitative approach within a post-positivist paradigm, adhering to grounded theory. Data collection techniques included participant observation and semi-structured interviews.Results: Through the triangulation of grounded theory and data analysis, the following findings emerged: • New ICTs have a significant impact on business strategies. • ICTs contribute to improved efficiency and effectiveness in business processes. • Digital-human configurations are essential, highlighting the relationship between human intelligence and technology and signaling the emergence of new job roles. • The adoption of technology has shifted from being optional to a fundamental and non-deferrable requirement for economic entities. • Business reinvention has become a key driver of excellence in response to current challenges.Conclusions: The use of ICT enhances an organization’s ability to manage and integrate data and documents across functional units. Information technologies increase organizational flexibility and job coherence. Intelligent organizations are characterized by their ability to adapt to change through technology and systems, fostering autonomy, self-responsibility, and improved performance. Organizations that leverage technology gain advantages in productivity and inclusion, ultimately adding value to their operations.